Is government (un)dead?: What apocalyptic fiction tells us about our view of public administration. Issue 3 (1st March 2017) - Smith-Walter, Aaron; Sharif, Fatima Sparger
Abstract : The zombie-plague apocalypse is a powerful social imaginary that focuses attention on the border between legitimate citizens and zombie "others." The surge in the number of zombie apocalypse films provides an illuminating area for studying the role imagined for public administration by popular culture. The response to zombies in apocalyptic films brings to fore new realities with the re-conceptualization of the legitimacy and authority of government. This re-conceptualization provides content for analyzing the portrayal of existing governmental institutions overwhelmed by the apocalypse, including local governments, the military, public health agencies, emergency services, and public utilities,